2006
DOI: 10.1021/np060279i
|View full text |Cite
|
Sign up to set email alerts
|

Abietane Diterpenoids from Salvia pachyphylla and S. clevelandii with Cytotoxic Activity against Human Cancer Cell Lines

Abstract: A phytochemical study has been carried out on the aerial parts of Salvia pachyphylla and S. clevelandii. From S. pachyphylla, the known diterpenes carnosol (2), rosmanol, 20-deoxocarnosol (3), carnosic acid, isorosmanol (4), 7-methoxyrosmanol, 5,6-didehydro-O-methylsugiol (5), 8beta-hydroxy-9(11),13-abietadien-12-one (6), 11,12-dioxoabieta-8,13-diene, and 11,12-dihydroxy-20-norabieta-5(10),8,11,13-tetraen-1-one were isolated, together with the new diterpene pachyphyllone (1). From S. clevelandii, the known dit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 22 publications
1
40
1
Order By: Relevance
“…To the opposite, concentrations of rosmarinic acid ranging from 6.25 to 50 lg/mL (139 lM) showed proliferative effects rather than cytotoxic activity (Yesil-Celiktas et al 2010). Carnosol exhibited growth inhibition 50 % (GI 50 ) values ranging from 3.6 to 26 lM in five tumor cells (Guerrero et al 2006). Also, Visanji et al (2006) reported IC50 values of 23 lM of carnosol for Caco-2 cells, a value close to the observed (34 lM) in prostate cancer cells after 72 h of treatment (Johnson 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To the opposite, concentrations of rosmarinic acid ranging from 6.25 to 50 lg/mL (139 lM) showed proliferative effects rather than cytotoxic activity (Yesil-Celiktas et al 2010). Carnosol exhibited growth inhibition 50 % (GI 50 ) values ranging from 3.6 to 26 lM in five tumor cells (Guerrero et al 2006). Also, Visanji et al (2006) reported IC50 values of 23 lM of carnosol for Caco-2 cells, a value close to the observed (34 lM) in prostate cancer cells after 72 h of treatment (Johnson 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several diterpenes including carnosol (42), rosmanol (46), 20-deoxocarnosol (43), carnosic acid (51), isorosmanol (44), 7-methoxyrosmanol (47), 5,6-didehydro-O-methylsugiol (55), 8b-hydroxy-9(11),13-abietadien-12-one (57), 11,12-dioxoabieta-8,13-diene (58), 11,12-dihydroxy-20-norabieta-5(10),8,11,13-tetraen-1-one (59) and pachyphyllone (60) isolated from S. pachyphylla as well as rosmadial (61), 16-hydroxycarnosol (45), abieta-8,11,13-triene (52), taxodone (62), 42, 46, and 51 isolated from S. clevelandii have shown efficacy against different human cancer cell lines (Table 1) (Guerrero et al 2006). Carnosol (IC 50 : 3.6-26.0 lM), 16-hydroxycarnosol (IC 50 : 3.6-35.0 lM) and 20-deoxocarnosol (IC 50 : 5.4-32.0 lM) were the most active components, however, no comparison was made with a known anticancer agent (Guerrero et al 2006).…”
Section: Biological Activitymentioning
confidence: 99%
“…Carnosol (IC 50 : 3.6-26.0 lM), 16-hydroxycarnosol (IC 50 : 3.6-35.0 lM) and 20-deoxocarnosol (IC 50 : 5.4-32.0 lM) were the most active components, however, no comparison was made with a known anticancer agent (Guerrero et al 2006).…”
Section: Biological Activitymentioning
confidence: 99%
“…These naturally occurring compounds display a vast array of biological activities including cytotoxic and antiproliferative activities against human tumor cells (Wang et al, 2007;Fronza et al, 2012). One of these compounds is taxodone which has been isolated from the aerial parts of Salvia clevelandii (Guerrero et al, 2006) and Salvia phlomoides (HuesoRodríguez et al, 1983) and displays cytotoxic effects and it is a relatively potent apoptotic inducer. Recently, we described how diterpenoids containing an abietane skeleton are strongly cytotoxic against human leukemia cells (Burmistrova et al, 2013).…”
Section: Parvifloron D Inhibits Cell Viability Of Human Tumor Cell Linesmentioning
confidence: 99%